2022
DOI: 10.3233/thc-202583
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a health education program in Asia, comparing Thailand, Indonesia, and Japan

Abstract: BACKGROUND: The global community is faced with aging societies, which will result in increased health care costs. we have been introducing our International Organization for Standardization (ISO)-certified health education system in Thailand and Indonesia. OBJECTIVE: The purpose of this study was to collect data on the effects of this ISO-certified health education system, to extend the healthy life expectancy and to study the feasibility of implementing this program and in new social contexts. METHODS: We imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…This slows down the response time of go-tasks and reduces the number of errors. An additional year of walking, on average 6,500-7,000 steps per day, has been shown to increase the reaction time on go/no-go tasks and reduce the number of errors (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This slows down the response time of go-tasks and reduces the number of errors. An additional year of walking, on average 6,500-7,000 steps per day, has been shown to increase the reaction time on go/no-go tasks and reduce the number of errors (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of 1,297 participants aged 60 -70 years across 20 geographies found that the number of steps taken by participants was correlated with anthropometry (r = 0.77, P < 0.001), physical fitness (r = 0.86, P = 0.008), and rate of improvement in brain function (r = 0.55, P < 0.021). Based on these results, it can be inferred that participants aged 60 years and older can improve their health if they walk an average of 7,000 steps or more per day (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metode Pengajaran, guru biasanya menggunakan metode pengajaran yang terstruktur dan interaktif. (Terasawa et al, 2022) mengatakan pada Sekolah Menengah Pertama (Chūgakkõ) berlangsung selama 3 tahun dan dimulai setelah SD selesai sekitar usia 12 tahun. Tujuannya yaitu mempersiapkan siswa untuk pendidikan menengah atas.…”
Section: Negara Jepang a Sistem Pendidikanunclassified